1991
DOI: 10.1073/pnas.88.10.4313
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Moloney murine leukemia virus-induced leukemia in transgenic mice expressing antisense RNA complementary to the retroviral packaging sequences.

Abstract: Recombinant plasmids pLP/as and pCP*as were constructed by positioning the Moloney murine leukemia virus (M-MuLV) proviral packaging (at) sequences in reverse orientation under the transcriptional regulation of lymphotropic promoter/regulatory elements from the M-MuLV long terminal repeat or the cytomegalovirus immediate-early region. Linear fragments containing the antisense 'I' and the appropriate transcriptional regulatory sequences from these plasmids were introduced into the mouse germ line by zygote micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…Even though the antisense molecules used are relatively short, the presence of the catalytic core, a structure conserved through evolution (Haseloff & Gerlach, 1988), may result in a more stable and effective antisense molecule. This result is also consistent with the published observation of an antisense effect for a longer 540 base antisense sequence to the corresponding MoMLV Ψ region in transgenic mice (Han et al, 1991).…”
Section: Table 1 Inhibition Of Replication Of Momlvsupporting
confidence: 82%
See 1 more Smart Citation
“…Even though the antisense molecules used are relatively short, the presence of the catalytic core, a structure conserved through evolution (Haseloff & Gerlach, 1988), may result in a more stable and effective antisense molecule. This result is also consistent with the published observation of an antisense effect for a longer 540 base antisense sequence to the corresponding MoMLV Ψ region in transgenic mice (Han et al, 1991).…”
Section: Table 1 Inhibition Of Replication Of Momlvsupporting
confidence: 82%
“…Interruption of this interaction has been shown to block the retroviral replication cycle and deletion mutants in this region are not packaged into virions (Sullenger et al, 1990). In previous studies (Han et al, 1991), antisense RNA complementary to the packaging region has been shown to inhibit virus replication in cell lines, and transgenic mice expressing the same antisense RNA to this region showed a reduction in both viraemia and the induction of leukaemia (Han et al, 1991).…”
mentioning
confidence: 99%
“…The hCMV-E/P (8) appeared most useful for our experiments, because this control element facilitated transgene expression in 28 tissues analyzed (13). Moreover, hCMV-driven transgenes were reproducibly shown to be highly expressed in spleen, thymus, and other lymphatic tissues (13,15,45).…”
Section: Mouse Lines Expressing Gag-snmentioning
confidence: 99%
“…This is the first transgenic mouse model for a proteinbased antiviral strategy. (A murine in vivo nucleic-acid-based antiviral strategy was described previously [15]. )…”
mentioning
confidence: 99%
See 1 more Smart Citation